Modeling farmers decisions on child labor and schooling in the cocoa sector: a multinomial logit analysis in Cote dIvoire - Nkamleu, G.B.; Kielland, A. (Wiley, 2006)
Since 2000, children working in the cocoa sector of Côte d'Ivoire have found themselves in the media spotlight. This situation has assumed particular importance because approximately 40% of the world's cocoa production occurs in Côte d'Ivoire. Concerned parties have since taken great interest in this thorny issue. There is a need to better understand the reality of child labor utilization in this sector. This article investigates child labor issues in the cocoa sector of Côte d'Ivoire in conjunction with schooling status of children. The study is based on a survey done in 2002, over a representative sample of more than 11,000 members of cocoa households. The multinomial logit model is used to capture choice probabilities across work and/or school options. The results reveal that child labor in cocoa farms and nonenrollment in schools are significant. Moreover, many children are involved in potentially dangerous and/or harmful tasks. Data also highlight gender and age dimensions in the participation of children in tasks and the way labor is allocated. Econometric results generally indicate that the gender and age of children, whether or not the child is the biological child of the household head, parents' education, the origin of the farmer, household welfare, household size, the household dependency ratio, the size of other perennial crop farms, the number of sharecroppers working with the household head, and communities' characteristics are all pertinent in explaining the child work/schooling outcome in the cocoa sector of Côte d'Ivoire.